THE DEVELOPMENT OF LECTORA INSPIRE BASED INTERACTIVE LEARNING MULTIMEDIA IN TEACHING WRITING RECOUNT TEXT FOR EIGHTH GRADE STUDENTS IN SMP NEGERI 35 MEDAN - Edi Rahmadani; Sumarsih Sumarsih (GENRE JOURNAL : Journal of Applied Linguistics of FBS Unimed, 2020)
The aim of this study was to develop the interactive learning multimedia by using lectora inspire for eight grade students at SMP Negeri 35 Medan. This study was conducted by using Research and Development (R & D) design through six stages; gathering data and information, need analysis, designing interactive learning multimedia, validating by the experts, revising and final product. The subject of the study was eighth grade students in SMP Negeri 35 Medan. The data were gathered by administering interview to an English teacher and distributing questionnaire to 29 respondents to get the students’ needs. The questionnaire result prove that the students need English media in learning writing which can stimulate students’ ability and develop writing skill. The product has been validated by an English lecturer and an English teacher with the interval was 4.6. The product was categorized as “Very Good” interactive learning multimedia of writing personal recount text as its positions in the interval . The final product of this study was an interactive learning multimedia of writing personal recount text in the form of an executable (.exe) packaged on a CD (compact disk).